2014
DOI: 10.1088/0963-0252/23/2/025007
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric particle fluxes from drifting ionization zones in sputtering magnetrons

Abstract: Electron and ion fluxes from direct current and high-power impulse magnetron sputtering (dcMS and HiPIMS) plasmas were measured in the plane of the target surface. Biased collector probes and a particle energy and mass analyzer showed asymmetric emission of electrons and of singly and doubly charged ions. For both HiPIMS and dcMS discharges, higher fluxes of all types of particles were observed in the direction of the electrons' E × B drift. These results are put in the context with ionization zones that drift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 44 publications
(83 reference statements)
2
54
0
Order By: Relevance
“…Such an observation was in fact made in Ref. 56 where we measured the same ion flux asymmetry for DCMS and HiPIMS discharges despite different directions of ionization zone motion for the two discharge modes.…”
Section: Spatial Distribution and Transport Of Ions And Implicatisupporting
confidence: 81%
See 2 more Smart Citations
“…Such an observation was in fact made in Ref. 56 where we measured the same ion flux asymmetry for DCMS and HiPIMS discharges despite different directions of ionization zone motion for the two discharge modes.…”
Section: Spatial Distribution and Transport Of Ions And Implicatisupporting
confidence: 81%
“…46 More specifically, it was suggested that electrons gain energy when crossing from the lowpotential side of the ionization zone to the high-potential side. These concepts have been so far supported by particle energy measurements 56 and by spectroscopically resolved snapshot-images of ionization zones. 57 Electron energization ("heating") is important since the energetic electrons produce ion-electron pairs and are therefore critical to sustaining the discharge.…”
Section: -12mentioning
confidence: 86%
See 1 more Smart Citation
“…18 Fast imaging of HiPIMS [2][3][4]11,19 and direct current magnetron sputtering 20 (dcMS) plasmas indicated that ionization rate and emission of light and particles are usually not uniformly distributed but concentrated in bright zones that move along the racetrack. Additionally, measurements of charged particle fluxes have revealed important features: (a) ion and electron fluxes appear in short pulses (jets), 21 (b) doubly charged ions have approximately twice the energy of singly charged ions, 18,21 and (c) ions emitted in the E× B direction have several 10 eV higher energy than ions going in the opposite direction, i.e., leaving the magnetron in the −E× B direction. 18 All of these features can be explained 18 assuming that an ionization zone is a locations of a potential hump of several 10 V. Consistent with Maxwell's equations, each potential hump is surrounded by an electric double layer.…”
mentioning
confidence: 99%
“…The time-averaged ion energy distributions (IEDFs) for 181 Ta + , 181 Ta 2+ , 40 Ar + and 40 Ar 2+ ion species measured from the DOMS plasma obtained at different peak powers for a MPPMS discharge. The Ar 2+ IEDs (figure 2b) exhibit a low energy peak centred close to 9 eV for both processes although the number of ions is almost one order of magnitude higher in DOMS than in DCMS.…”
Section: Ion Energy Distribution Functionsmentioning
confidence: 99%